Assessment of the adaptive potential of the plum-tree to the conditions of the winter period in the northern forest-steppe of the Southern Urals - Slepneva Tatyana (EDP Sciences, 2021)
The results of assessment are presented the stability of 13 sorts of plum-tree P. salicina subsp. ussuriensis Koval. et Kost. to the climatic conditions in the winter period from 2015/16 to 2020/21 in the northern forest-steppe of the Southern Urals. Like the control sort Ural’skaya zolotistaya by high adaptability to the conditions of the winter period are characterized sorts Altajskaya yubilejnaya, Zavet, Pionerka, Sapfir, Seyanec Krasnogo shara, Sodruzhestvo, Sinil’ga, Ural’skie zori, Chernosliv pozdnij. Stable fruiting over the years, regardless of weather conditions, during the flowering period with a yield of 62.0 to 91.6 hundredweight/ha are mark out with an increasing total sort Altajskaya yubilejnaya, Pionerka, Chernosliv pozdnij. The control sort Ural’skaya zolotistaya exceeds the yield of the sort Altajskaya yubilejnaya (91.6 hundredweight/ha), at the level of control the yield of the sorts Sodruzhestvo (71.5 hundredweight/ha), Sapfir (70.0 hundredweight/ha).